ChemInform Abstract: New Clerodane Diterpenoids from the Twigs and Leaves of Croton euryphyllus. Issue 29 (July 2015) - Pan, Zhenghong; Ning, Desheng; Wu, Xingde; Huang, Sisi; Li, Dianpeng; Lv, Shihong
Abstract isolation and structure elucidation of three new clerodane diterpenoids (I)‐(III)